PENGARUH DUKUNGAN ATASAN DAN MOTIVASI TERHADAP EMPLOYEE ENGAGEMENT DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI ( STUDI PADA KECAMATAN MIJEN KOTA SEMARANG ): PENGARUH DUKUNGAN ATASAN DAN MOTIVASI TERHADAP EMPLOYEE ENGAGEMENT DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI ( STUDI PADA KECAMATAN MIJEN KOTA SEMARANG ) - Trishendratmo, Kurniawan; Rijanti, Tristiana (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to examine and evaluate the impact of organizational culture as a moderating variable on employee engagement in the Mijen District of Semarang City, as well as the influence of superior support and motivation. This kind of study is known as explanatory research. 106 of the 117 ASN employees in the Mijen District (districts and villages) returned the questionnaire, making up the research population. A Likert scale questionnaire that complied with factor analysis and Cronbach's Alpha reliability and validity standards was the tool utilized to collect the data. The following conclusions were drawn from the data analysis: (1) The first hypothesis test findings indicate a positive and substantial relationship between superior support and employee engagement. (2) The findings of the second hypothesis test demonstrate a strong and favorable relationship between employee engagement and motivation. (3) The third hypothesis test's findings support the positive and significant relationship between team member engagement and superior support by demonstrating a moderate organizational culture. (4) The fourth hypothesis test's findings support the positive and significant relationship between team member engagement and motivation by demonstrating a moderate organizational culture.